Treating advanced breast cancer - Cáceres G., Eduardo (2015)
Breast cancer is one of the most common forms of cancer in women, it ranks third as a cause of cancer death in the city of Lima, and the second in the incidence of female cancers. But despite the best efforts to achieve an early diagnosis of breast cancer, through physician education and public education particularly with the recommendation of self breast examination by women, yet the diagnosis it is delayed and therefore advanced breast cancer and inoperable thus constitutes a major problem whose magnitude can be a precious when we consider that in our series, 39 percent of patients when viewed in the first query are inoperable and 50 percent of operated will recurrences or spread of the disease during the first three years following the operation, which means that in the course of this time, nearly 70 percent of patients live with advanced breast cancer.